2013
DOI: 10.1007/s12639-012-0226-9
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of canine visceral leishmaniasis in southeast of Iran

Abstract: Visceral leishmaniasis is an endemic disease in many parts of Iran and infected dogs constitute the main domestic reservoirs that play a key role in transmission to humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
3
11
0
Order By: Relevance
“…ELISA is a highly applicable technique that is characterised by high sensitivity, but its specificity depends on the antigen. The specificity and sensitivity of the ELISA test that was employed to detect CanL in this investigation were 99.1% and 98.5%, respectively [21].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…ELISA is a highly applicable technique that is characterised by high sensitivity, but its specificity depends on the antigen. The specificity and sensitivity of the ELISA test that was employed to detect CanL in this investigation were 99.1% and 98.5%, respectively [21].…”
Section: Discussionmentioning
confidence: 68%
“…Enzyme-linked immunosorbent assay (ELISA) and indirect fluorescent antibody tests (IFAT) are the most widely used serological methods [20]. ELISA shows potential as a sensitive tool for mass screening in epidemiological studies and is suited to field conditions [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Leishmania genus is an intracellular protozoan that infects the macrophage and dendritic cell lineages of their vertebrate host (Naderer and McConville 2008). Leishmania genus accounts for a group of diseases accompanied by a broad range of clinical manifestations together known as leishmaniasis (Goto and Lindoso 2012;Mahshid et al 2014). Leishmania infantum is one of the main causes of visceral leishmaniasis (VL) (Hatam et al 1997;Mohammadi-Ghalehbin et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is endemic in Iran, with an average prevalence of 14.2%, and variations according to the region: 18.2% in northeast, 12.3% in the central region, and 4.4% in Southeastern Iran [41]. Another study, restricted to southwestern Iran, found a prevalence of 15.4% [42]. In China, VL is an anthropozoonosis which completes its life cycle in dogs, raccoons, coatis, and children [12].…”
Section: Geographic Distribution and Prevalencementioning
confidence: 99%